A Checklist for Zooplankton of Eastern and Southeastern Anatolia Regions (Turkey) - Hilal Bulut; Serap Saler (Düzce Üniversitesi Bilim ve Teknoloji Dergisi)
A checklist on Turkey zooplankton was published by Ustaoğlu in 2004 and totaly 427 species were reported. Among the zooplankton species in this checklist, 229 species recorded from Rotifera, 106 from Copepoda and 92 from Cladocera. The checklist of Rotifera published in 2012, reported 341 rotifer taxa. During the years since the last checklist process, many studies especially in Eastern and Southeastern Anatolia region of Turkey have been carried out and in this study we have prepared a current zooplankton checklist of Turkish inland waters in these regions. In all these regions 185 zooplankton species have been recorded to date.